Tradução e adaptação transcultural do instrumento Spiritual Assessment Scale no Brasil - Freitas, Elizangela Oliveira; Vieira, Margarida Maria da Silva; Tsunemi, Miriam Harumi [UNESP]; Pessini, Leocir; Guerra, Grazia Maria (My University, 2013)
Spirituality is considered an integrant part of nursing care. This study aimed to perform a cross-cultural adaptation of the “Spiritual Assessment Scale” (SAS) to Brazil. A specific instrument for cross-cultural adaptation based on Lynn’s studies (Likert scale) was developed. The first step consisted in the application of the instrument developed by the authors to assess the SAS by 6 “experts” in the area of Spirituality and Nursing and with 11 patients from the clinical medical unit to review the SAS instrument with 21 questions. After conducting statistical tests, the questions were considered appropriate for use in the research as demonstrated by Cronbach’s alpha, which indicated an acceptable reliability of the instrument. It can be stated that in both groups (experts and patients) internal consistency was high, the characteristics of the original scale were preserved even after the stages of translation and adaptation to Brazil.

Considera-se a espiritualidade parte integrante da assistência de enfermagem. Este estudo objetivou realizar a adaptação transcultural do instrumento “Spiritual Assessment Scale” (SAS) para o Brasil. Foi desenvolvido um instrumento específico para a adaptação transcultural basedo nos estudos de Lynn (escala de Likert). A primeira etapa consistiu na aplicação do instrumento desenvolvido pelos autores para avaliação da SAS com 6 experts da área de Espiritualidade e Enfermagem e com 11 pacientes da unidade de clínica médica, para avaliação do instrumento SAS com 21 questões. Após a realização de testes estatísticos, as questões estavam adequadas para a aplicação na pesquisa, como demonstrado pelo coeficiente alfa de Cronbach, que indicou uma confiabilidade aceitável do instrumento. Pode-se afirmar que em ambos os grupos (expert e pacientes) a consistência interna foi elevada, mantendo as características da escala original, após as etapas de tradução e adaptação para o Brasil.
Translation and cross-cultural validation of the instrument Spiritual Assessment Scale in Brazil
Keywords: Nursing; Spirituality; Validation studies; Enfermagem; Espiritualidade; Estudos de validação